A new insight on reciprocal relationship between microRNA expression and epigenetic modifications in human lung cancer - Roghayeh Sheervalilou; Sakine Shirvaliloo; Sedigheh Fekri Aval; Amir Mahdi Khamaneh; Akbar Sharifi; Khalil Ansarin; Nosratollah Zarghami (Tumor Biology)
Lung cancer stands among the leading causes of cancer-related death in the world. Although the molecular network implicated in lung cancer development is extensively revealed, the mortality rate is only slightly improved. MicroRNAs are small, endogenous single-stranded evolutionary conserved non-coding RNAs which involve in a wide variety of biological processes including cell growth, proliferation, metabolism, and differentiation. MicroRNAs, as novel biomarkers, have multiple functions in normal lung tissue development, and aberrant expression profiles of certain microRNAs could induce lung tumorigenesis. Similar to that of protein-coding genes, microRNA expression and function are regulated by multiple factors as well as the epigenetic network including DNA methylation and histone modification mechanisms. Furthermore, microRNAs can themselves regulate key enzymes which drive epigenetic modifications and have a pivotal effect on the cell biology. In this review, we will look into the regulatory loop linkage between microRNA expression and epigenetic modifications, and then, we will discuss the effects of epigenetics on the miRNome, as well as the role of epi-microRNAs in controlling the epigenome in human lung cancer. Better knowledge of reciprocal connection between microRNAs and epigenome will help to develop novel microRNA-orientated diagnostic, prognostic and therapeutic strategies related to human lung cancer in future.